Coupling mechanisms for split ring resonators: Theory and experiment - Hesmer, F; Tatartschuk, E; Zhuromskyy, O; Radkovskaya, A; Shamonin, M; Hao, T; Stevens, C; Faulkner, G; Edwards, D; Shamonina, E; Hao, T; Stevens, C; et al. (2007)
We study experimentally and theoretically coupling mechanisms between metamaterial elements of the split ring resonator (SRR) type. We show that, depending on the orientation of the elements relative to each other, the coupling may be either of magnetic or electric type or a combination of both. Experimental results on SRRs with resonances around 1.7 -1.9 GHz agree quantitatively with results of simulations (CST Microwave Studio). Further simulations provide analysis for a variety of SRRs both in the GHz and in the 20 THz frequency regions. The variety of coupling mechanisms can be employed in designing near field manipulating devices based on propagation of slow waves. © 2007 WILEY-VCH Verlag GmbH and Co. KGaA.